2015
DOI: 10.1016/j.jfluchem.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and chemical characterization of products from hydrolysis of UF6

Abstract: A c c e p t e d M a n u s c r i p t 1 HIGHLIGHTS  UF 6 hydrolysis was carried out under reaction conditions that were water deficient for preparation of UO 2 F 2 products. SEM Images of products of UF 6 hydrolysis deposited onto carbon conducting tape and aluminum tape showed different morphologies.  Morphologies of material deposited on aluminum after hydrolysis of UF 6 and stored under high humidity conditions change after one week.  Chemical characterization by powder X-ray diffraction analysis and -Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Uranyl fluoride (UO 2 F 2 ), produced by the hydrolysis of UF 6 , is another intermediate in the deconversion of UF 6 to UO 2 . Solid UO 2 F 2 will precipitate out whenever UF 6 is allowed to come into contact with moisture [6][7][8]-for example, when UF 6 gas lines are not sufficiently dry or if a storage cylinder has been structurally compromised.…”
Section: +mentioning
confidence: 99%
“…Uranyl fluoride (UO 2 F 2 ), produced by the hydrolysis of UF 6 , is another intermediate in the deconversion of UF 6 to UO 2 . Solid UO 2 F 2 will precipitate out whenever UF 6 is allowed to come into contact with moisture [6][7][8]-for example, when UF 6 gas lines are not sufficiently dry or if a storage cylinder has been structurally compromised.…”
Section: +mentioning
confidence: 99%
“…It is not possible to determine if either the schoepite phases are redistributing between different schoepite phases without changing the ratio of UO 3 :H 2 O due to dissolution and precipitation during storage over this time, or progressing from one schoepite phase to another. Material stored under the lower temperature conditions (1 or 3) appears to be clumped/massive conglomerates of sub-rounded and irregular clumps that included fines and scale decorations [1,2]. Image of S1, L1, and L2 reveal that changes in the morphology were particularly notable following storage under higher relative humidity and temperature (Condition 4).…”
Section: Legacy Samplesmentioning
confidence: 99%
“…Material storage under controlled temperature and relative humidity Aging vessels fabricated from Swagelok fittings are described elsewhere [1,2,21]. The four storage conditions of temperature and relative humidity used in these experiments were: Condition 1 (5°C and 25 %), Condition 2 (37°C and 15 %), Condition 3 (5°C and 97 %), and Condition 4 (37°C and 89 %).…”
Section: Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The spherical shape and size strongly indicates UO 2 F 2 . Several studies have shown that formation of UO 2 F 2 from UF 6 in a humid environment results in spherical shapes of about ≅0.2-2.0 μm diameter [33][34][35]. The presence of nitrogen is slightly surprising, but could be explained by attachment of nitrogen-rich materials present in the atmosphere.…”
Section: All Workhops -Aerosol Morphologymentioning
confidence: 99%